Trend Analyses of Temperature and Rainfall and Their Response to Global CO2 Emission in Masha, Southern Ethiopia - Fedhasa Benti; Magarsa Abara (Caraka Tani: Journal of Sustainable Agriculture, 2019)
Ethiopia is one of the most vulnerable countries to climate change and often signifies higher probabilities of droughts that have historically affected millions of farmers. The variability in rainfall patterns and drought have disrupted crop production and exacerbated food insecurity in many parts of Ethiopia. This study aimed to investigate seasonal and annual temperature and rainfall trends and their association to the global CO2 emission. Temperature and rainfall data obtained from the Masha meteorological station and CO2 from EDGAR 4.3.2 dataset recorded for 36 years. The Linear regression model was used to analyse seasonal temperature and rainfall trends. Pearson’s correlation coefficient employed to measure the relationship between temperature and rainfall and global CO2 emission. The results showed that there were significant warming trends of seasonal and annual mean temperatures while summer season and annual rainfall significantly declined. The prediction results showed that the summer and annual mean temperatures would be significantly increased while the rainfall decreased for the next 35 years. The cumulative global CO2 and annual mean temperature and rainfall were correlated significantly at P = 0.0004 and 0.006 for temperature and rainfall, respectively. The results demonstrated clearly that the increasing of temperature and the decreasing of rainfall had a direct relationship with the global CO2 emissions and suggested that there should be a sound soil and water management, short season seed supply and pipe irrigation practices to reduce the future crop damage in the area.